## You are here

Homeproof of Stewart's theorem

## Primary tabs

# proof of Stewart’s theorem

Let $\theta$ be the angle $\angle AXB$.

Cosines law on $\triangle AXB$ says $c^{2}=m^{2}+p^{2}-2pm\cos\theta$ and thus

$\cos\theta=\frac{m^{2}+p^{2}-c^{2}}{2pm}$ |

Using cosines law on $\triangle AXC$ and noting that $\psi=\angle AXC=180^{\circ}-\theta$ and thus $\cos\theta=-\cos\psi$ we get

$\cos\theta=\frac{b^{2}-n^{2}-p^{2}}{2pn}.$ |

From the expressions above we obtain

$2pn(m^{2}+p^{2}-c^{2})=2pm(b^{2}-n^{2}-p^{2}).$ |

By cancelling $2p$ on both sides and collecting we are led to

$m^{2}n+mn^{2}+p^{2}n+p^{2}m=b^{2}m+c^{2}n$ |

and from there $mn(m+n)+p^{2}(m+n)=b^{2}m+c^{2}n$. Finally, we note that $a=m+n$ so we conclude that

$a(mn+p^{2})=b^{2}m+c^{2}n.$ |

Related:

StewartsTheorem,ApolloniusTheorem,CosinesLaw, ProofOfApolloniusTheorem2

Type of Math Object:

Proof

Major Section:

Reference

Parent:

Groups audience:

## Mathematics Subject Classification

51-00*no label found*

- Forums
- Planetary Bugs
- HS/Secondary
- University/Tertiary
- Graduate/Advanced
- Industry/Practice
- Research Topics
- LaTeX help
- Math Comptetitions
- Math History
- Math Humor
- PlanetMath Comments
- PlanetMath System Updates and News
- PlanetMath help
- PlanetMath.ORG
- Strategic Communications Development
- The Math Pub
- Testing messages (ignore)

- Other useful stuff